SI-ATRP grafting of polymers from polydopamine-modified cellulose nanocrystals - Hou, Yelin; Zhang, Zhen; Harrisson, Simon; Sèbe, Gilles (Carbohydrate polymers, 2024)
This work reports on the possibility of using polydopamine (PDA) as a tool to immobilize bromoisobutyryl moieties at the surface of cellulose nanocrystals (CNCs) and initiate Surface Intitiated Atom Transfer Radical Polymerization (SI-ATRP) reactions from these sites. Two different strategies based on i) the stepwise modification of the CNCs with dopamine (DA) and α-bromoisobutyryl bromide (BiBB) (Protocol 1) and ii) the one-step treatment of the CNCs with a mixture of DA and BiBB-modified DA (Protocol 2), were compared. Only the CNC particles treated according to Protocol 1 guaranteed efficient anchoring of the SI-ATRP initiating sites in our experimental conditions (with limited impact on the CNCs crystalline structure), the coated layer being leached out by certain solvents in the case of Protocol 2. The brominated particles displaying the best performances were subsequently tested as potential ATRP macroinitiators, using methyl methacrylate (MMA) and styrene (St) as model monomers. Polymer-grafted particles were successfully obtained, with a grafting density twice as high for Sty as for MMA, demonstrating the validity of this strategy. [Display omitted]